Examining Social Media Public Sentiment: Youtube Response to 2024 Indonesian Presidential Debate - Syam, Andi Armayudi; Afdal, Andi Ahmad Malikul (Universitas Muhammadiyah Makassar, 2024)
This research aims to analyze public sentiment on YouTube social media regarding the 2024 Indonesian presidential candidate debate. The method used is sentiment analysis using big data analysis with the help of Nvivo. The data used are public comments contained in the 2024 Indonesian presidential candidate debate video on YouTube. The research results show that the majority of public sentiment towards the 2024 Indonesian presidential candidate debate is positive. However, there are also several comments that are negative and neutral. The theme most discussed by the public in the 2024 Indonesian presidential candidate debate is